Optimal Asset Allocation and Risk Shifting in Money Management - Basak, Suleyman; Pavlova, Anna; Shapiro, Alexander (Review of Financial Studies, 2007)
This article investigates a fund manager's risk-taking incentives induced by an increasing and convex relationship of fund flows to relative performance. In a dynamic portfolio choice framework, we show that the ensuing convexities in the manager's objective give rise to a finite risk-shifting range over which she gambles to finish ahead of her benchmark. Such gambling entails either an increase or a decrease in the volatility of the manager's portfolio, depending on her risk tolerance. In the latter case, the manager reduces her holdings of the risky asset despite its positive risk premium. Our empirical analysis lends support to the novel predictions of the model.